Investigating the use of podcasts in an open, distance and e-learning environment (Perspectives in Education, 2020)
In a world where the podcast stands out as one of the important support technologies for online learning, lecturers face great challenges in the delivery of podcasts in a qualitative and productive way. The introduction of podcasts into distance teaching and learning has often failed to meet the expected outcomes, and the educational landscape (Dede, 2008) contains evidence of students who have been unable to benefit from this innovation. Therefore, the aim of this paper was to explore the types of podcasts that lecturers at an open and distance an e-learning institution use for teaching and learning in the courses they teach. The focus was to explore how lecturers can use high-quality podcasting to meet students learning expectations in open, distance and e-learning institutions.